'n Hamer, 'n saag en 'n skroewedraaier - oor metodes van ontleding van die griekse teks van die nuwe testament - Botha, J. (Koers, 1986)
In this article four methods of analysis of the Greek text of the New Testament are compared. The methods are: South African Discourse Analysis, the method of Syntactic Structural Analysis, the method of the Analysis of Thought Structure and finally the method of Semantic Analysis based on nuclear structures.